Evidence-informed urban health and sustainability governance in two Chinese cities. Issue 1 (28th June 2021) - Pineo, Helen; Zhou, Ke; Niu, Yanlin; Hale, Joanna; Willan, Catherine; Crane, Melanie; Zimmermann, Nici; Michie, Susan; Liu, Qiyong; Davies, Michael
Sustainable development is best supported by intersectoral policies informed by a range of evidence and knowledge types ( e.g . scientific and lay). Given China's rapid urbanisation, scale and global importance in climate mitigation, this study investigates how evidence is perceived and used to inform urban health and sustainability policies at central and local levels. Well-informed senior professionals in government/scientific agencies (12 in Beijing and 11 in Ningbo) were interviewed. A thematic analysis is presented using deductive and inductive coding. Government agency participants described formal remits and processes determining the scope and use of evidence by different tiers of government. Academic evidence was influential when commissioned by government departments. Public opinion and economic priorities were two factors that also influenced the use or weight of evidence in policymaking. This study shows that scientific evidence produced or commissioned by government was routinely used to inform urban health and sustainability policy. Extensive and routine data collection is regularly used to inform cyclical policy processes, which improves adaptive capacity. This study contributes to knowledge on the 'cultures of evidence use'. Environmental governance can be further improved through increased data-sharing and use of diverse knowledge types. Policy relevance: Insights are provided into the 'cultures of evidence use' in urban sustainability and health governance in two Chinese cities, noting the complex interconnections between national policy agendas, the public and evidence. Policies are centrally led and informed by officially commissioned scientific evidence. Environmental health data were used for monitoring policy implementation, and they were interpreted with careful consideration of public opinion and economic priorities. There were opportunities for local priorities to shift the policy agenda, particularly when the public became aware of a specific environmental health threat. Environmental governance could be strengthened in these settings through increased cross-sector data-sharing and integration of diverse knowledge types. A strength of China's approach is routine data collection that feeds a monitoring and policy cycle rarely achieved elsewhere. This cycle provides feedback to government departments, allows policy adjustment over time and can inform decisions during crises.